2009
DOI: 10.1002/glia.20883
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of P2Y receptors on Müller cells of the postnatal rat retina

Abstract: In the postnatal and mature retina, many processes are controlled by the action of nucleotides. Their effects are partly mediated via activation of metabotropic P2Y receptors. However, little is known about the developmental regulation and cellular localization of P2Y receptor subtypes. Combining immunohistochemical and neurophysiological methods, we investigated the developmental expression of P2Y receptors on Müller cells, the principal macroglial cells of the retina. The P2Y(1) and the P2Y(4) receptors, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…*p<0.05 and **p<0.01 compared to control. Bar=20 μm ADP-sensitive P2Y 1 receptors were previously described in Müller glial cells [22], a finding that is corroborated by our present observation that ADP induces intracellular calcium increases in Müller cells growing at the edge of the scratch in the cultures. Moreover, although MRS2179, a specific antagonist of P2Y 1 receptors, significantly decreased ADPinduced proliferation of glial progenitors in early developing retinal cultures, this compound did not affect the growth of glia in the scratched cultures, reinforcing our hypothesis that UTP preferring P2Y 2 /P2Y 4 receptors are the sites involved in the growth of glia to the scratched area.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…*p<0.05 and **p<0.01 compared to control. Bar=20 μm ADP-sensitive P2Y 1 receptors were previously described in Müller glial cells [22], a finding that is corroborated by our present observation that ADP induces intracellular calcium increases in Müller cells growing at the edge of the scratch in the cultures. Moreover, although MRS2179, a specific antagonist of P2Y 1 receptors, significantly decreased ADPinduced proliferation of glial progenitors in early developing retinal cultures, this compound did not affect the growth of glia in the scratched cultures, reinforcing our hypothesis that UTP preferring P2Y 2 /P2Y 4 receptors are the sites involved in the growth of glia to the scratched area.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, although Muller cells from adult human and rat retinas express transcripts for both P2Y 2 and P2Y 4 receptors [17], only immunoreactivity for the P2Y 4 receptor protein was detected in Muller cells from the rodent retina [22], suggesting that these cells express only the P2Y 4 UTP-sensitive receptor subtype. In the present work, we detected the P2Y 2 receptor protein with an antiserum against the rat P2Y 2 receptor in extracts from purified chick retinal glial cultures.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Given that previous studies in human M€ uller glia showed ionotropic P 2 X-mediated components, [27][28] we tested whether P 2 X receptors might contribute to the [Ca 2C ] i response associated with SOCE. Activity of the P 2 Y-IP 3 pathway was minimized by blocking Ca 2C flux through intracellular release channels with the SERCA (sarcoplasmic endoplasmic reticulum Ca 2C ATPase) antagonist cyclopiazonic acid (CPA; 5 mM).…”
Section: Resultsmentioning
confidence: 99%
“…P2Y 1 receptors are the principal receptors on Müller glial cells [25], but they are also expressed by cholinergic amacrine cells [26]. It has previously been shown that ATP stimulates proliferation of neural retinal progenitor cells in the embryonic chicken retina [27,28].…”
Section: Discussionmentioning
confidence: 99%